Psychometric validity, and measurement invariance of the PERMA model among youth in Malaysia - Ramli, Siti Aisyah; Zaremohzzabieh, Zeinab; Idris, Khairuddin; Bolong, Jusang; Abdullah, Haslinda (Cogent OA, 2024)
PERMA is a multidimensional well-being model that has contributed greatly to the well-being of people and communities. This research aimed to create the PERMA instrument, which measures the five dimensions of well-being in Malaysia: positive emotions, engagement, positive relationships, meaning in life, and accomplishment, and to assess its factor structure, reliability, and measurement invariance. This study included 550 Malaysians between the ages of 18 and 30 years old (M = 28.49, SD = 6.18). The sample was randomly split into two groups for exploratory factor analysis and confirmatory factor analysis to explore the PERMA model. The revised model revealed satisfactory internal consistency and reliability. Additionally, this study examined the measurement invariance of the PERMA model through gender, education, and marriage groups by multigroup confirmatory factor analysis. The findings revealed that measurement invariance was obtained across gender and education categories. This instrument uses multidimensional conceptualization to offer researchers studying youth well-being in Malaysia a specialized tool to assess and increase youth well-being levels. Eventually, the goal is for this tool to assist Malaysian youth in developing a deeper sense of self by identifying their talents and shortcomings and discovering strategies to thrive in life fully.